Synthesis and cytotoxic evaluation of some new 3-(2-(2-phenylthiazol-4-yl) ethyl)-quinazolin-4(3H) one derivatives with potential anticancer effects - Leila Hosseinzadeh; Alireza Aliabadi; Mohsen Rahnama; Hamid Mir Mohammad Sadeghi; Marzieh Rahmani Khajouei (Wolters Kluwer Medknow Publications, 2017)
Quinazolinones are a group of heterocyclic compounds that have important biological activities such as cytotoxicity, anti-bacterial, and anti-fungal effects. Thiazole-containing compounds have also many biological effects including antitumor, antibacterial, anti-inflammatory, and analgesic activities. Due to significant cytotoxic effects of both quinazoline and thiazole derivatives, in this work a group of quinazolinone-thiazol hybrids were prepared and their cytotoxic effects on three cell lines were evaluated using MTT assay. Compounds A3, A2 , B4 , and A1 showed highest cytotoxic activities against PC3 cell line. Compounds A3 , A5 , and A2 were most active against MCF-7 and A3 , A5 , and A6 showed good cytotoxic effect on HT-29 cell line. According to the results, A3 efficiently inhibited all cell growth tested in a dose dependent manner. The IC 50 of A3 was 10 M, 10 μM, and 12 μM on PC3, MCF-7, and HT-29 cells, respectively.